DETERMINAN KEANDALAN INFORMASI LAPORAN KEUANGAN DENGAN TIME PRESSURESEBAGAI PEMODERASI (Studi pada Satuan Kerja di Wilayah Kerja KPPN Mataram) - Zulfirman Switriansyah; Prayitno Basuki; Endar Pituringsih (Universitas Negeri Malang, 2015)
This study aimed to examine the effect of apparatus competencies, utilization of informationtechnology, and implementation SAP of accrual basis to the reliability of financial reporting informa-tion that presented by government. As well as to examine the effect of time pressure as moderating therelationship of independent variables on the reliability of financial reporting information. The popula-tion in this study are all Unit Ministry/Agency in the payment area of KPPN Mataram. Samples weretaken using a technique Slovin at the level of error rate by 10% and distributed through a purposivesampling with criteria work units which has the largest budget ceiling. Data obtained by distributingquestionnaires to 76 respondents who are officials/officers directly responsible for the preparation offinancial statements work units or with positions as arranger financial statements. Analysis of datausing Moderated Regression Analysis (MRA). The results showed that the apparatus competencies,utilization of information technology, and implementation SAP of accrual basis has a positive effect onthe reliability of financial reporting information. The higher apparatus competencies, utilization ofinformation technology and implementation SAP of accrual basis, the higher the information reliabilitylevel of government financial statements. While time pressure only moderate the relationship betweenthe implementation SAP of accrual basis with the reliability of financial reporting information. Mean-while time pressure can’t moderate the relationship between the apparatus competencies and the utili-zation of information technology to the reliability of financial reporting information.Keywords:reliability information, competence, information technology, accrual basis, time pressure